Earthquake-induced loss assessment of steel dual concentrically braced structures subjected to near-field ground motions. (May 2023) - Khademi, Mohsen; Tehranizadeh, Mohsen; Shirkhani, Amir; Hajirasouliha, Iman
Abstract: Steel structures with dual systems, including special moment-resisting frames (SMRFs) and special concentrically braced frames (SCBFs), have found extensive applications in seismically active regions due to their considerable lateral stiffness and ductility. However, the seismic performance of such system has not been investigated subjected to near-field ground motion records. To address this research gap, this paper evaluates collapse risk and earthquake-induced loss of multi-story steel structures with dual concentrically braced frames. A comprehensive seismic performance assessment is conducted on selected five-, 10-, and 15-story structures subjected to near-field ground motions (NF-GMs) with and without pulses based on the methodology provided in FEMA P-58. The results are also used to assess the effect of NF-GMs with pulses on the seismic performance measures, such as life-cycle cost and repair time of the studied structures at different seismic intensity levels. Finally, the contribution rate of collapse and demolition of structures, and contribution of structural and nonstructural members in the repair cost and time of the steel structures are estimated and compared subjected to NF-GMs. It is concluded that collapse and demolition loss play significant roles for NF-GMs with and without pulses, respectively, while the seismic collapse behavior is governed by the ratio of the pulse period of the GM to the period of the first mode of the structure.